EFEKTIVITAS AROMATERAPI PEPPERMINT TERHADAP FREKUENSI EMESIS GRAVIDARUM PADA IBU HAMIL DI PMB MURTINAWITA TAHUN 2023 - Nanda Putri, Dwi; Pitriani, Risa; Damayanti, Ika Putri (Ensiklopedia of Journal, 2025)
Pregnancy is a case that occurs on a woman. Some of the discomfort felt by pregnant women is caused by the physiological adaptation period of the pregnant woman's body to her pregnancy. The biggest contributing discomfort is nausea and vomiting so that 60-70% of pregnant women experience nausea and vomiting ( emesis gravidarum ). Emesis gravidarum is is a feeling of dizziness, flatulence and body feeling tired accompanied by discharge of stomach contents with a frequency of less than 5 times a day. One of the treatments using non-pharmacological therapy is giving peppermint aromatherapy. The purpose of this study was to determine the effectiveness of peppermint aromatherapy on the frequency of emesis gravidarum in trimester pregnant women at PMB Murtinawita in 2023. This research design used a pre-experimental design with a One Group Test Post Test. The research was conductes at PMB Murtinawita, Pekanbaru City. In this study used purposive sampling by considering inclusion and exclusion criteria with total sample 19 people. The data were collected through sheet PUQE-24 checklist. The collected data were analyzed by Wilcoxon test. The findings of this study revealed that the results Wilcoxon test obtained that There is influence gift aroma therapy peppermint to frequency emesis gravidarum ( p-value = 0.000). Then, the results of external variables obtained from statistical results using the chi-square test p-value>o,o5 show that there is no relationship between age, occupation and parity with incident emesis gravidarum. Hopefully, PMB Murtinawita, Pekanbaru City waiting room and examination room will use aromatherapy and students will be able to make aromatherapy products in appropriate technology courses and future researchers can provide aromatherapy with diffusers and aromatherapy candles. Keywords : Pregnant Mother, Emesis gravidarum , Aromatherapy Peppermint